Integration of Psychosocial Factors as Correlates to Critical Thinking Ability in Graduate Students - Sakdapat, Naksit; Bhanthumnavin, Duchduen (Dusit Thani College Journal, 2020)
This correlation-comparative study was based on the interactionism model as the conceptual research framework. The study aimed to investigating the important predictors in terms of psychological characteristics and situational factors on critical thinking and the at-risk groups. The samples were students the total of 451 second-year graduate students, which obtained by multi-stage sampling method. The research consisted 11 questionnaires in the form of summated rating scales. The reliability of alpha coefficient of questionnaires were between .61 to .85. Multiple regression analysis results revealed that all 10 predictors from the groups of the situational factor, the psychological trait, and the psychological state, can be operated for prediction on critical thinking 42.8% in the total sample. The important predictors in attitude toward academic identity, future directions in control, core self evaluation, academic old habits and academic alignment. The at-risk groups were weekend graduate students. The results from this study can shed the light on the development at-risk groups of students and can be a basis for further research.